Epithelioid hemangioendothelioma of the liver—case report - Hrabar, Josip; Kavur, Lovro; Vidjak, Vinko; Hrabar, Martina; Bubić, Vinko (Digestive Medicine Research, 2019)
Epithelioid hemangioendothelioma of the liver (EHL) is a rare vascular tumor of unknown etiology and unpredictable biological outcome. We describe the case of a 59-year-old Caucasian male patient admitted to University Hospital Merkur for diagnostic work-up and liver transplantation (LT). The patient was presented with sudden loss of consciousness, fatigue and right upper abdominal pain. The only laboratory abnormality was mild increase of transaminases. The MSCT of the abdomen and pelvis showed multiple hypervascular lesions throughout the liver, and the ultrasound-guided biopsy confirmed the pathohistological diagnosis. An orthotopic LT was performed, and the patient was clinically well, without any signs of hepatic transplant dysfunction or tumor recurrence a year after. Multifocality is a common feature of EHL, therefore LT was the treatment of choice. As the multislice computed tomography (MSCT) or magnetic resonance (MR) presentation is frequently inconclusive, the final diagnosis of the tumor has to be confirmed histologically to avoid misdiagnosis of a metastasis or other liver tumors.